Hubungan Tingkat Pengetahuan dengan Motivasi Ibu Hamil Melakukan Konseling HIV/AIDS di Klinik Kandungan RSUD Dr. Doris Sylvanus Palangka Raya: The Relationship of Knowledge Level with Motivation of Pregnant Mothers to Conduct HIV/AIDS Counseling in Obtency Clinics Dr. Doris Sylvanus Palangka Raya - Rabiatunnisa Rabiatunnisa; Hermanto Hermanto; Seli Mutia Handriani (Jurnal Surya Medika (JSM), 2022)
Quality HIV (Human Immunodeficiency Virus) counseling is an effective component as a preventive effort to promote changes in sexual behavior to reduce HIV transmission. Pregnant women must know and understand to be motivated to do HIV/AIDS counseling as an effort to prevent HIV/AIDS transmission. But in reality, the motivation of pregnant women to do HIV counseling tends to be low, because pregnant women do not feel they have a vulnerability to HIV/AIDS transmission. This study was conducted to determine the relationship between the level of knowledge and the motivation of pregnant women to do HIV/AIDS counseling at the Obstetrics Clinic at RSUD dr. Doris Sylvanus Palangka Raya. This research uses correlation research with cross-sectional approach and non-probability sampling technique (accidental sampling). Respondents in this study amounted to 61 respondents who met the inclusion criteria. The data was collected using a questionnaire which was then analyzed using the sperman rank statistical test. From the 61 respondents, the results of statistical analysis showed that the level of knowledge of pregnant women was in the sufficient category 24 (39%), good category 21 (34%), poor category 16 (26%) and motivation of pregnant women in the medium category 38 (62%), strong category 16 (26%), weak category 7 (11%) with p value = 0, 000 (p < 0, 05). There is a significant and significant relationship between the level of knowledge and the motivation of pregnant women in conducting HIV/AIDS counseling at the Obstetrics Clinic of RSUD dr. Doris Sylvanus.